العنف ضد المرأة، أسبابه، وأساليب علاجه - أحمد, حمزه يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
المرأة هي نصف المجتمع الذي ينجب ويربي النصف الآخر، ورفع الظلم عن المرأة هو رفعه عن المجتمع كله فهي المجتمع بأكمله ، ومن هنا كان تحرر المرأة هو تحرر للأوطان، والإنسان حيث لا يمكن للأم المستعبدة أن تنجب ولداً متحرراً، ولا يمكن للأم المريضة أن تنجب صحيح الجسم ، والعقل ، ولهذا كان لا بد من توجيه الأنظار إلى ضرورة الاهتمام بالمرأة، وخلق المناخ الملائم الذي يساعدها في الخروج من بوتقة الجهل والظلام إلى ساحة العلم والنور، وتهيئة الظروف المناسبة التي تمكنها من تطوير نفسها، وبالتالي تطوير كل المجتمع . لذا يجب أن يكف الرجل عن ممارسة العنف ضدها ، فهذا الأمر يشل قدرتها على الحياة، وعلى الشعور بالكرامة والإنسانية ، وإذا لم يقتنع بهذا الأمر فيجب إجباره بكافة الوسائل، والطرائق الممكنة . Women is the half of society, which born and grow the second half, so take-up the oppression on women men to take-up it on whole society , because the women is the whole society, so the freedom of women is the freedom of country and human, where the thrall mother cannot born freedom child , and sick mother cannot born healthy body, and mind child, so we must be attention toward necessary care of women ,and create suitable climant ,which help her to egress from the crucible of blindness, and darkness toward the court of science , and light supply the suitable circumstance, which command her to developed herself , and subsequently to developed the whole society, so man must stop to uses the Violence against women, because these thing disrupt her capability to life, and to feel her dignity, and humanity, but if he did not belief in these thing ,so we must constraint him by all possible procedure ,or methods